Est16, a New Esterase Isolated from a Metagenomic Library of a Microbial Consortium Specializing in Diesel Oil Degradation - Pereira, Mariana Rangel [UNESP]; Mercaldi, Gustavo Fernando; Maester, Thais Carvalho [UNESP]; Balan, Andrea; Macedo Lemos, Eliana Gertrudes de [UNESP] (Public Library Science, 2015)
Lipolytic enzymes have attracted attention from a global market because they show enormous biotechnological potential for applications such as detergent production, leather processing, cosmetics production, and use in perfumes and biodiesel. Due to the intense demand for biocatalysts, a metagenomic approach provides methods of identifying new enzymes. In this study, an esterase designated as Est16 was selected from 4224 clones of a fosmid metagenomic library, revealing an 87% amino acid identity with an esterase/lipase (accession number ADM63076.1) from an uncultured bacterium. Phylogenetic studies showed that the enzyme belongs to family V of bacterial lipolytic enzymes and has sequence and structural similarities with an aryl-esterase from Pseudomonas fluorescens and a patented Anti-Kazlauskas lipase (patent number US20050153404). The protein was expressed and purified as a highly soluble, thermally stable enzyme that showed a preference for basic pH. Est16 exhibited activity toward a wide range of substrates and the highest catalytic efficiency against p-nitrophenyl butyrate and p-nitrophenyl valerate. Est16 also showed tolerance to the presence of organic solvents, detergents and metals. Based on molecular modeling, we showed that the large alpha-beta domain is conserved in the patented enzymes but not the substrate pocket. Here, it was demonstrated that a metagenomic approach is suitable for discovering the lipolytic enzyme diversity and that Est16 has the biotechnological potential for use in industrial processes.